2020
DOI: 10.1002/humu.24032
|View full text |Cite
|
Sign up to set email alerts
|

TRPV6 variants confer susceptibility to chronic pancreatitis in the Chinese population

Abstract: Chronic pancreatitis (CP) is a progressive fibroinflammatory syndrome of the pancreatic tissue caused by genetic and environmental factors. Previously reported susceptibility genes in CP explain less than half of the apparent heritability. To uncover novel pathogenic mechanisms, we initially performed low‐coverage whole‐genome sequencing on 464 Chinese CP patients and 504 controls. The transient receptor potential cation channel, Subfamily V, Member 6 (TRPV6) gene was found to be significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Chronic pancreatitis (CP) is a complex disease that can be caused by genetic and/or environmental factors 1-3 . Since the mapping and cloning of the first gene found to underlie hereditary pancreatitis (i.e., PRSS1 ; MIM# 276000) more than 20 years ago 4-7 , multiple additional genes/loci associated with CP have been identified, either by means of candidate gene approaches 8-17 or hypothesis-free (‘agnostic’) approaches 18-22 .…”
Section: Main Textmentioning
confidence: 99%
“…Chronic pancreatitis (CP) is a complex disease that can be caused by genetic and/or environmental factors 1-3 . Since the mapping and cloning of the first gene found to underlie hereditary pancreatitis (i.e., PRSS1 ; MIM# 276000) more than 20 years ago 4-7 , multiple additional genes/loci associated with CP have been identified, either by means of candidate gene approaches 8-17 or hypothesis-free (‘agnostic’) approaches 18-22 .…”
Section: Main Textmentioning
confidence: 99%
“…Decreased mRNA and protein levels of TRPV6 have been found in placentas of women suffering from pre-eclampsia 25 . Several human TRPV6 gene mutations have been recently linked to transient neonatal hyperparathyroidism, skeletal under-mineralization and dysplasia, and chronic pancreatitis 26 32 . Because of the central role of calcium in cancer development 33 , TRPV6 has also been classified as an oncochannel that is involved in both increased cell proliferation and inhibition of apoptosis 34 , and overexpressed in various types of human cancer, including breast, prostate, colon, ovarian, thyroid, endometrial cancers, and leukemia 33 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, two research groups showed that loss of function variants of TRPV6 are associated with risk of chronic pancreatitis in patients from Japan, Germany, France and China [26,27]. During our research towards identification of novel CP susceptibility genes using a whole exome sequencing approach, we also found overrepresentation of the novel defective TRPV6 variants in Polish CP pediatric patients (data unpublished, [75]).…”
Section: Trpv6mentioning
confidence: 74%
“…In nonalcoholic early-onset CP, TRPV6 variants contribute to disease pathogenesis in 1.5-4% of the patients [26,27]. Since it is speculated that TRPV6 plays a role in Ca 2+ removal from the ducts, the loss-of-function variants could cause elevated ductal Ca 2+ concentration, which would stimulate autoactivation of trypsinogen and increased trypsin activity.…”
Section: Trpv6mentioning
confidence: 99%